Influence of thermophysical properties on magnetite water-based ferrofluid heat transfer at sphere surface under magnetic field and thermal radiation - Siti Hanani, Mat Yasin; Muhammad Khairul Anuar, Mohamed; Zulkhibri, Ismail; Mohd Zuki, Salleh (VINČA Institute of Nuclear Sciences, 2022)
This theoretical study investigated the effect of thermophysical properties on Nusselt number when the magnetic field and thermal radiation are exposed to the ferrofluid flow at the lower stagnation point of a hot sphere surface. The thermophysical properties are important mechanisms considered in the heat transfer process. Besides, the ferroparticles volume fraction is one of the variables that can enhance the thermophysical properties that are exclusively studied on thermal conductivity and thermal diffusivity of ferrofluid. Therefore, the correlation between the ferroparticles volume fraction and thermophysical properties is measured by the Pearson product-moment correlation coefficient method. The strength of association and the direction of the relationship between these pertinent variables are exhibited in ferrofluid flow composed of magnetite (Fe3O4) and water (H2O). Regression analysis is implemented to predict the effect of the ferroparticles volume fraction on the Nusselt number. The results show a positive correlation between ferroparticles volume fraction and thermal conductivity as well as between ferroparticles volume fraction and thermal diffusivity. Furthermore, a simple linear regression model proposed to predict the Nusselt number when increasing the ferroparticles volume fraction resulted in statistically significant and given minuscule residuals value.